The role of journalism in the fight against terrorism - السالم, حمدان خضر (ALBAHITH ALALAMI, 2015)
The media plays an important role in a number of functions performed by them. Press is one of those media which had and still have a clear role in addressing the various issues, topics, and events. Journalism is no longer as expressed by owners of the liberal theory – it seeks to raise the instincts – but it began to excite the minds of readers to meet their needs. At the same time, it does not neglect the search for the truth and work to deliver it to readers. Some have identified a set of tasks carried out by the press including the interest in public affairs, the needs of the community, work to provide happiness, what is beneficial and useful and combat the negative phenomenon and to address the deviations facing society. The comics as one of the journalists› arts has an influential role in achieving the objectives of the press through its ability to deliver the communicative message carried by those lines, colors, and short words associated with them to have an impact on the recipient, who claimed the corner looking for caricature in the newspapers to feel happiness and enjoy the contours of his characters as well as the ideas it contains and topics addressed by the bold critic style. And terrorism today represents the greatest challenge and the imminent threat to the community and spreading violence, destruction, and vandalism under the rationales and justifications. It was obliged for the cartoonists to address the imminent danger and highlights showdown by its tools, means, and technical methods that exposed the terrorist acts. The cartoonist has tried to dispel the aura that made terrorism for itself and showed the real ugly face and dropped his claims and counterfeit detection finality claims and behaviors that has nothing to do with humanity.